A new inter-cloud service-level guarantee protocol applied to space missions. (2017) - Kaddouri, Ali; Guezouri, Mustapha; Mbarek, Nader
Nowadays, the term cloud computing often falsely assumes the availability of an unlimited pool of resources. On the contrary, if a cloud provider reaches its limits, it may pose the risk of breaking their service level agreement (SLA). Space agencies could start using the cloud computing model within their IT infrastructure with multiple ground control points around the world to reduce the cost. An inter-cloud communication protocol with a guarantee of the service level will significantly reduce the cost if each ground control segment is considered as a cloud provider. This paper outlines a new protocol that was developed to take into consideration the end-to-end service-level guarantee. The protocol defines new structures and functionalities instead of the commonly used BGP as a baseline. The paper presents the results of a performance evaluation study concerning the convergence time and the data overhead as well as the ability of the protocol to support any domain-specific services. The results are highly positive, showing the scalability of the solution. The application of our proposal within the space industry also proved to be a suitable means for experimentation of the protocol.